Characteristics of hydrogen-related fatigue fracture in 2Mn-0.1C martensitic steel. (29th October 2021) - Matsumiya, Hisashi; Shibata, Akinobu; Okada, Kazuho; Tsuji, Nobuhiro
Abstract: This study investigated the hydrogen-related fatigue fracture in 2Mn-0.1C steel having a lath martensite microstructure. The presence of hydrogen significantly reduced the fatigue life. The transgranular surface was a main component in each stress range of the uncharged specimen, while the intergranular surface was frequently observed in the hydrogen-charged specimen. The crystallographic orientation analysis by electron backscattering diffraction revealed that the cracks mainly propagated along {011} planes regardless of the presence of hydrogen. Compared with the uncharged specimen, however, plastic deformation was localized near the fatigue crack in the hydrogen-charged specimen. According to the reconstructed fracture process by fracture surface topography analysis, the hydrogen-related fatigue fracture was discontinuous and composed of isolated nucleation of intergranular cracks and quasi-cleavage crack propagation initiated at the pre-existing intergranular cracks. Highlights: H-related fatigue fracture in as-quenched martensitic steel was studied. H significantly reduced the fatigue life of martensitic steel. IG surface was frequently observed in the H-charged specimen. Fatigue cracks mainly propagated along {011} planes regardless of the presence of H. IG fracture occurred in isolation, followed by QC fracture in the H-charged specimen.